Pembebanan Pajak Penghasilan pada Pendaftaran Tanah untuk Pertama Kali - Erviana, Irma; Aspan, Zulkifli; Nur, Sri Susyanti (Al-Ishlah: Jurnal Ilmiah Hukum, 2021)
This study aims to determine the imposition of income tax on the transfer of rights to land and/or buildings on land registration for the first time. This research was conducted using empirical legal research methods with data collection techniques through observation, interviews, and literature. In addition, this research uses the descriptive analysis method. The results of this study indicate that the imposition of income tax on the transfer of rights to land and/or buildings on land registration for the first time is not a requirement for applicants for rights related to land registration for the first time. However, the Bone Regency Land Office requires proof of payment of income tax on the transfer of rights to land and/or buildings to the applicant during the land registration application for the first time. Thus, the imposition of income tax on the transfer of rights to land and/or buildings to the applicant regarding land registration for the first time at the Bone Regency Land Office is considered contrary to Article 4 section (1) of Law No. 36 of 2008 jo. Article 4 section (1) Government Regulations No. 34 of 2016. Therefore, it is hoped that the Head of the Bone Regency Land Office will abolish the requirement for the imposition of income tax on the transfer of rights to land and/or buildings to applicants for rights related to land registration for the first time. Apart from that, eliminating these requirements also avoids the imposition of inappropriate or on target taxes to uphold aspects of justice and legal certainty (the principle of certainty).